Petroleum Industry Act (PIA), Transnational Corporations (TNCs) and the Prospects of Peace and Development in the Niger Delta - Eze, Prince; Okonkwo, Nnamdi (University of Nigeria Journal of Political Economy, 2022)
Given the Host Community Development Trust Fund as provided for by the PIA in which host communities will be funded with 3% of the Opex of upstream players, this study using data generated through secondary sources and Marxist Political Economy as a framework for analysis, examined the prospects of peace returning to the Delta and the underdevelopment narrative of the region becoming a thing of the past. Findings from the study revealed that, just like other noble initiatives and interventions adopted in the Delta, given the nature and character of the Nigerian State this new legislation may not yield the expected result because of poor implementation and corruption. The elites who often see any opportunity to serve the public, as a medium for personal enrichment as well as, insincerity on the part of the TNCs and the Government will also serve as a setback to the PIA. Among other things, 100 per cent implementation of the PIA is recommended. It is also recommended that host communities must elect people with track records of integrity, honesty, transparency and capacity to represent them on the management committee of the host communities’ development trust.